Medical decision-making in acute care: philosophy and approach - Taylor, Robin (Henry Stewart Talks, 2021)
Medical Decision-Making, Acute Care, End-Of-Life Care, Death, Hospital Care, Good Standards Framework Proactive Identification Guidance, Prognosis